The effect of marinated duck meat using turmeric with modified cassava flour as an encapsulant - Harvey Febrianta; Anis Usfah Prastujati; Dave Mangindaan (International Journal of Science and Environment (IJSE), 2025)
Duck meat is a type of food that is quite popular in the public because the texture of the meat is quite soft and tastes delicious. The availability of duck meat is quite a lot at a very affordable price. Lipid components in duck meat are easily damaged due to oxidation and caused by pathogenic bacteria, so it is necessary to maintain the quality with the addition of turmeric which is encapsulated in modified cassava flour. The research process was carried out by marinating duck meat with turmeric coated in modified cassava flour as an encapsulant (TMC), then the meat was stored at a chilling temperature of 36°F for 8 days. The test parameters including moisture, pH value, peroxide value (PV), and sensory. The treatments observed consisted of control (SA), duck meat marinated with 2% TMC (SB), duck meat marinated with 4% TMC (SC), duck meat marinated with 6% TMC (SD). The results observed that moisture, pH value, peroxide value (PV) with a shelf life of up to 8 days had a significant interaction (P<0.05). This study concluded that TMC was able to inhibit oxidative damage without degrading the sensory quality in duck meat stored for 8 days at chilling temperature 36°F. Keywords: Duck meat, encapsulation, marination, modified cassava flour, turmeric.